Optimization of Hatch Cover Maintenance on MV. Orient King - Rafigo Charisma Maulana; Samsul Huda; Dyah Ratnaningsih; I'ie Suwondo (Journal of Engineering Science and Technology Management, 2026)
The hatch cover is a critical structural component of a general cargo vessel, designed to safeguard cargo from seawater ingress and maintain watertight integrity. This study evaluates the constraints affecting the execution of planned hatch cover maintenance aboard MV. Orient King. A qualitative single-case study design was employed over a 12-month onboard observation period. Data was collected through semi-structured interviews with three key deck personnel (Chief Officer, Bosun, and Able Seaman), structured operational observations, and a review of maintenance logs. Thematic analysis of the data revealed that maintenance compliance is fundamentally hindered by aggressive marine corrosion, a brittle supply chain causing 2-to-3-month lead times for critical spare parts (e.g., rubber packing, hydraulic hoses), and a dense operational tempo that routinely forces the deferral of scheduled Planned Maintenance System (PMS) tasks. Consequently, temporary repairs are frequently substituted for permanent solutions, elevating the risk of cargo damage. To mitigate these risks, this paper proposes a prioritized action plan, emphasizing strict adherence to the company's Safety Management System (Document No. JSP E41), optimized spare-part inventory control, and enhanced supervisory protocols.